GIS Education for Spatial Thinking and Environmental Literacy: A Bibliometric-Systematic Review - Yuniza Maqfirah; Muhammad Irham; Ichwana Ichwana (Borneo Research and Education Center, 2026)
The growing integration of Geographic Information Systems (GIS) and geospatial technologies into education has created new opportunities for developing spatial thinking, environmental literacy, and sustainability competencies. However, research on GIS-based learning remains fragmented across geography education, environmental education, spatial thinking, and geospatial technology studies, limiting a comprehensive understanding of its intellectual structure and educational implications. This study examines the development, thematic evolution, and educational contributions of GIS-based spatial learning through a bibliometric-systematic review approach. Data were collected from the Scopus database using a structured search strategy covering the period 2020 to 2026. A total of 167 publications met the bibliometric inclusion criteria, while 72 studies were selected for thematic synthesis following the PRISMA 2020 framework. Bibliometric analysis was conducted using VOSviewer to examine publication trends, scientific productivity, keyword networks, and thematic clusters, while thematic synthesis was employed to identify major educational themes and emerging research directions. The findings reveal a significant increase in GIS-based educational research, particularly after 2023. Science mapping identified four dominant knowledge clusters related to geography education, spatial thinking, environmental sustainability, and educational technology. Thematic synthesis further revealed five major themes: GIS-based spatial learning, spatial thinking development, environmental literacy and sustainability education, remote sensing and geospatial environmental learning, and action-oriented learning. Notably, action-oriented learning emerged as the most prominent direction, indicating a shift from technology-centered approaches toward participatory, inquiry-based, and problem-solving pedagogies. This study proposes an integrative conceptual framework linking geospatial technologies, spatial thinking, environmental literacy, action-oriented learning, and sustainability competencies, with implications for educational innovation, curriculum development, and future action research in geography, science, and environmental education.